2020
DOI: 10.1088/2053-1591/ab70df
|View full text |Cite
|
Sign up to set email alerts
|

High pressure anomalies in exfoliated MoSe2: resonance Raman and x-ray diffraction studies

Abstract: Detailed high pressure Resonance Raman (RR) Spectroscopy and x-ray diffraction (XRD) studies are carried out on 3-4 layered MoSe 2 obtained by liquid exfoliation. Analysis of ambient XRD pattern and RR spectra indicate the presence of a triclinic phase along with its parent hexagonal phase. Slope change in the linear behavior of reduced pressure (H) with respect to Eulerian strain ( f E ) is observed at about 13 GPa in hexagonal phase and at about 17 GPa for the triclinic phase. High pressure Raman measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 43 publications
3
12
0
Order By: Relevance
“…Similar bulk modulus values are also observed in other transition metal dichalcogenides in their triclinic phase. 25,26 The fitting of the Eulerian strain vs normalized pressure in the study by Wang et al taking 8.9 GPa unit-cell volume as reference volume produced a bulk modulus of 90:1 + 2:2 GPa and a pressure derivative of 5:1 + 0:3, and the value of bulk modulus in their study is found to be very close to the present study. 18 We have shown the EOS fitting in Fig.…”
Section: Journal Of Applied Physicssupporting
confidence: 84%
See 4 more Smart Citations
“…Similar bulk modulus values are also observed in other transition metal dichalcogenides in their triclinic phase. 25,26 The fitting of the Eulerian strain vs normalized pressure in the study by Wang et al taking 8.9 GPa unit-cell volume as reference volume produced a bulk modulus of 90:1 + 2:2 GPa and a pressure derivative of 5:1 + 0:3, and the value of bulk modulus in their study is found to be very close to the present study. 18 We have shown the EOS fitting in Fig.…”
Section: Journal Of Applied Physicssupporting
confidence: 84%
“…Pressure induced strain has a very important role in changing the structural and the electronic properties of materials. 25,26,[42][43][44] To see the response of strain in our sample, we have estimated Eulerian strain (f E ) and corresponding normalized pressure (H) using the following equations: 42,45…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%
See 3 more Smart Citations